Studi Tentang Pelaksanaan Layanan Bimbingan Kelompok Untuk Menurunkan Prasangka Sosial Pada Peserta Didik Kelas XI Jurusan IPA Dan IPS di MAN Model Palangka Raya: Study On The Implementation Of Guidance Services groups To Reduce Social Preliminary In Class Xi Students Of Science And Ips Department In Palangka Raya Model Man - Siti Cilik Windiani; Diplan Diplan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to determine how the role of guidance and counseling teachers in reducing social prejudice in students using group guidance services in Palangka Raya Model MAN. The implementation of this study uses a qualitative approach. While the method used by researchers to uncover the problem in this study is the case study method. Data collection is done using the method of observation, interviews, and documentation. The objects in this study are BK teachers, homeroom teachers, subject teachers, and students. The objectives of this study are: (1) Knowing the progress of the group guidance service program in schools conducted by BK teachers, (2) Knowing the progress and changes that occur in participants students after being given group guidance services to reduce their social prejudices